1999
DOI: 10.1093/nar/27.13.2806
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acid (PNA) binding-mediated induction of human  -globin gene expression

Abstract: Peptide nucleic acids (PNAs) can bind to homopurine/homopyrimidine sequences of double-stranded DNA targets in a sequence-specific manner and form [PNA]2/DNA triplexes with single-stranded DNA D-loop structures at the PNA binding sites. These D-loop structures have been found to have a capacity to initiate transcription in vitro. If this strategy can be used to induce transcription of endogenous genes, it may provide a novel approach for gene therapy of many human diseases. Human [beta] globin disorders such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 25 publications
1
62
0
2
Order By: Relevance
“…In an earlier study (38), the level of γ-globin expression was increased in K562 cells using triple helix-forming PNA targeted to a homopurine region at the −300 region of γ-globin promoter. However, this study was not a true reactivation test, and neither site-specific binding in vivo nor efficiency of cell/nuclear entry were monitored.…”
Section: Discussionmentioning
confidence: 95%
“…In an earlier study (38), the level of γ-globin expression was increased in K562 cells using triple helix-forming PNA targeted to a homopurine region at the −300 region of γ-globin promoter. However, this study was not a true reactivation test, and neither site-specific binding in vivo nor efficiency of cell/nuclear entry were monitored.…”
Section: Discussionmentioning
confidence: 95%
“…In comparison, the binding of PNAs to single-stranded targets such as mRNA or single-stranded DNA targets is not affected by the presence of salts. For example, in our previous studies the presence of 150 mM KCl, which is relevant to the physiological K + concentration, significantly inhibited the binding of PNA-1 to the target [35].…”
Section: The Effects Of Salts On Pna Bindingmentioning
confidence: 77%
“…Early studies revealed that the PNA binding-generated D-loops could initiate transcriptions in vitro using T7 RNA polymerase [34]. The work of our laboratory demonstrated that the PNA binding-generated D-loops could initiate transcription in a HeLa nuclear extract in vitro transcription system and induce a GFP reporter gene expression in the CV-1 monkey kidney cells [35]. Most importantly, when PNAs designed to bind to the human γ-globin gene 5' untranslated region (5' UTR) sequence were used to treat the K562 human erythroleukemia cells, transcription of the endogenous γ-globin gene from the PNA binding sites was achieved [35].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…13,14) The binding characteristics and sequence specificity of TFOs give these oligonucleotides vast potential in gene modification, such as inhibition of gene expression, inhibition of replication, and induction of site-specific mutagenesis. [15][16][17][18][19][20][21][22][23][24][25] However, there are a number of obstacles to TFO activity under physiologic conditions. [26][27][28][29] Recent developments in nucleoside and oligonucleotide analogue chemistry show great promise for solving the problems of TFO bioactivity and target options.…”
mentioning
confidence: 99%